Liquid crystal polymer, composition for heat dissipation members using the same, and material for electronic components
Patent Information
- Application Number
- JP2021114749
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-16
- Filing Date
- 2021-07-12
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-07-12
AI Technical Summary
【0009】 上記ポリマーは液晶性を示すため、ポリマー鎖同士の絡み合いが少ない。従ってこのポリマーを用いた放熱部材は、高い熱伝導性を持つ。また該ポリマーの架橋性基を反応させることにより得られる硬化物は、耐熱性が高い。そこで、本発明のポリマーは、パワー半導体用などの放熱材料として、好適に使用できる。
Smart Images

Figure 0007651988000001 
Figure 0007651988000002 
Figure 0007651988000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystalline polymer, and a composition for heat dissipation members and a material for electronic components each using the same. [Background technology]
[0002] In recent years, there has been a demand for packaging materials with high thermal conductivity to prevent the temperature of the internal semiconductors from becoming too high in semiconductor elements for power control in hybrid and electric vehicles, CPUs for high-speed computers, etc. In other words, the ability to effectively dissipate heat generated by the semiconductor chip to the outside has become important.
[0003] One method for solving this heat dissipation problem is to bring a highly thermally conductive material (heat dissipation component) into contact with the heat-generating area, leading the heat to the outside and dissipating it. Examples of materials with high thermal conductivity include inorganic materials such as metals and metal oxides. However, these inorganic materials have problems with processability and insulation, making it very difficult to use them alone as a filler for semiconductor packages. For this reason, development is underway to create heat dissipation components with high thermal conductivity by combining these inorganic materials with resins.
[0004] In general, the thermal conductivity of composite materials has been increased by adding a large amount of inorganic fillers, such as metal fillers, to general-purpose resins, such as polyethylene resins, polyamide resins, polystyrene resins, acrylic resins, and epoxy resins. However, the thermal conductivity of inorganic fillers is a value specific to each material and has a set upper limit. Therefore, methods for increasing the thermal conductivity of resins to achieve this have been widely attempted. As a means for actually achieving this, for example, a method using an epoxy composition, such as that described in Patent Document 1, is known.
[0005] However, the epoxy resin obtained by using the composition disclosed in Patent Document 1 has low heat resistance. Therefore, there are problems in practical use, particularly in semiconductor element applications for power control. In addition, when the epoxy resin is used by laminating other resins, there are problems such as low resistance to the solvent of the resin to be laminated. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2019-123834 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an epoxy resin having high thermal conductivity, heat resistance and solvent resistance, and to provide an epoxy resin composition which provides said epoxy resin. [Means for solving the problem]
[0008] As a result of intensive research, the present inventors have found that a linear polymer obtained from an epoxy compound and a curing agent, which has a temperature range in which it exhibits liquid crystallinity between 100°C and 200°C and at the same time has a crosslinkable functional group, can solve the above-mentioned problems, and have completed the present invention. Effect of the Invention
[0009] The polymer exhibits liquid crystallinity, so that the polymer chains are less likely to be entangled. Therefore, a heat dissipation member using this polymer has high thermal conductivity. Furthermore, a cured product obtained by reacting the crosslinkable groups of the polymer has high heat resistance. Therefore, the polymer of the present invention can be suitably used as a heat dissipation material for power semiconductors and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0011] The present invention includes the following items.
[0012] [1] A linear polymer obtained from an epoxy compound and a curing agent. It has a temperature range between 100°C and 200°C and exhibits liquid crystallinity. It also has crosslinkable functional groups.
[0013] [2] The polymer according to item [1], wherein the epoxy compound comprises a compound represented by formula (1) and the curing agent comprises a compound represented by formula (2). TIFF0007651988000001.tif52107In formula (1), R 1 is an alkylene having 2 to 12 carbon atoms, At this time, R 1 -CH not adjacent to 2 - may be replaced by -O-, -CH 2 -Ga-CF 2 May be replaced with -. In formula (2), R 2 are independently hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, or a group represented by the following formula (3): At this time, R 2 At least one of the above is a group represented by formula (3), and n is an integer of 0 to 3. TIFF0007651988000002.tif2648 In formula (3), R 3 are independently hydrogen or alkyl having 1 to 12 carbon atoms, and * represents the bonding position to the aromatic ring.
[0014] [3] In the compound represented by formula (1), R 1 is an alkylene having 4 to 12 carbon atoms, and in the compound represented by formula (2), n is an integer of 2 or 3. The polymer according to item [2].
[0015] [4] A composition comprising the polymer according to any one of items [1] to [3].
[0016] [5] The composition according to item [4], further comprising an inorganic filler.
[0017] [6] The composition according to item [5], wherein the inorganic filler is aluminum oxide or boron nitride.
[0018] [7] A semi-cured sheet using the composition according to any one of items [4] to [6].
[0019] [8] A heat dissipation member obtained by curing the composition according to any one of items [4] to [6].
[0020] [9] A monomer composition of an epoxy compound and a curing agent that gives the polymer according to any one of items [1] to [3].
[0021] The phrase "at least one hydrogen atom in the ring may be replaced by an alkyl group having 1 to 10 carbon atoms" means, for example, an embodiment in which at least one of the hydrogen atoms at the 2-, 3-, 5- and 6-positions of 1,4-phenylene is replaced by a substituent such as fluorine or methyl. "Compound (1)" means a compound represented by formula (1), and may also mean at least one compound represented by formula (1).
[0022] As described above, the problem of the present application can be solved by using a linear polymer obtained from an epoxy compound and a curing agent, which has a temperature range from 100°C to 200°C in which it exhibits liquid crystallinity, and which also has a crosslinkable functional group.
[0023] In the present invention, a linear polymer is a polymer with little or no branching or crosslinking in the polymer chain structure. Such a polymer is generally obtained by reacting a bifunctional epoxy compound with a bifunctional curing agent. If the polymer chain has a large amount of crosslinking, the polymer loses liquid crystallinity and solubility in a solvent.
[0024] The polymer has a structure in which a portion called a liquid crystal core, which is a series of aromatic rings or alicyclic rings, is connected by a flexible linking group such as alkylene. The liquid crystal core and the linking group are constructed by reacting an epoxy compound as a raw material with a curing agent. In this case, the liquid crystal core and the linking group may each be derived from an epoxy compound or a curing agent. However, from the viewpoint of ease of synthesis, it is preferable to design the polymer so that the liquid crystal core is derived from a curing agent and the linking group is derived from an epoxy compound.
[0025] The temperature at which the linear polymer exhibits liquid crystallinity is between 100°C and 200°C. The temperature at which the liquid crystallinity is exhibited may be the entire range of this temperature range, or may be a part of the range. In this case, in order to improve the heat resistance of the heat dissipation member after the composition of the present application is cured, it is preferable that the temperature range at which the liquid crystallinity is exhibited is as high as possible. On the other hand, in order to reduce the influence on other members used simultaneously with the heat dissipation member, it is preferable that the curing temperature is low. In addition, it is preferable to cure the heat dissipation member of the present invention at a temperature at which the liquid crystallinity is exhibited in order to improve the characteristics. Therefore, from this viewpoint, it is preferable that the temperature range at which the liquid crystallinity is exhibited is also low. Furthermore, the temperature at which the polymer exhibits liquid crystallinity may change slightly depending on the components such as the solvent contained in the polymer. The temperature at which the liquid crystallinity is exhibited may be in a range that includes such changes.
[0026] As the curing agent of the present invention, all known curing agents can be used, such as phenol-based, compounds obtained by acylation of the hydroxyl group of a phenol-based curing agent, amine-based, thiol-based, carboxylic acid-based, etc. However, it is preferable to use a phenol-based curing agent, since it is easy to obtain a linear polymer and a polymer having high heat resistance can be obtained.
[0027] As the functional group capable of being crosslinked in the present application, a group that crosslinks itself by heating or the like may be selected, or a group that crosslinks via other additives may be selected. In the former case, the group may be crosslinked by an initiator. Examples of such crosslinking groups include vinyl, acryl, ethynyl, allyl, vinyloxy, etc. Among these, it is preferable to select vinyl because it has high reactivity and the crosslinked structure does not decompose due to heat.
[0028] The vinyl is a group in which vinyl or vinyl H is substituted with a monovalent organic group. In this case, there is no limit to the number of vinyl substitutions, but in order to improve heat resistance, it is preferable that the vinyl is unsubstituted or monosubstituted. There is also no limit to the substitution position of the vinyl group.
[0029] A preferred structure of the polymer of the present invention is disclosed below. The preferred structure of the polymer of the present invention is obtained by polymerizing a raw material containing a compound of the following formula (1) as an epoxy compound and a compound of the following formula (2) as a curing agent.
[0030] TIFF0007651988000003.tif52107
[0031] In formula (1), R 1 is an alkylene having 2 to 12 carbon atoms, where R 1 -CH not adjacent to 2 - may be replaced by -O-, -CH 2 -Ga-CF 2 - may be replaced by In formula (2), R 2 are independently hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, or a group represented by the following formula (3), in which R 1 At least one of the above is a group represented by formula (3), and n is an integer of 0 to 3. TIFF0007651988000004.tif2648
[0032] In formula (3), R 3are independently hydrogen or alkyl having 1 to 12 carbon atoms, and * represents the bonding position to the aromatic ring.
[0033] In the above formula (1), R 1 is an alkylene having 2 to 12 carbon atoms. 1 -CH not adjacent to 2 - may be replaced by -O-, -CH 2 -CF 2 In order to exhibit liquid crystallinity of the polymer, R 1 The number of carbon atoms in R is preferably 4 or more, and more preferably 6 or more. 1 As the number of carbon atoms in R increases, the softening point of the polymer decreases. 1 The number of carbon atoms is preferably 10 or less, and more preferably 8 or less.
[0034] In formula (2), n is an integer of 0 to 3. In this case, in order to develop liquid crystal properties of the polymer, n is preferably 1 or more, and more preferably 2 or more.
[0035] In formula (2), the number of vinyl is at least 1, but in order to exhibit liquid crystallinity of the polymer, 1 to 2 is preferable, and 1 is the most preferable. For the same reason, the other R 3 is preferably hydrogen or methyl, more preferably hydrogen.
[0036] The polymer of the present invention is polymerized using 10 mol % or more of the compound of formula (1) based on the total epoxy compounds. In this case, in order to improve the liquid crystallinity of the polymer, it is preferable to use 30 mol % or more of the compound of formula (1), and more preferably 50 mol % or more.
[0037] The polymer of the present invention is polymerized using 10 mol% or more of the compound of formula (2) based on the total epoxy compounds. In this case, in order to improve the liquid crystallinity of the polymer and to improve the heat resistance of the material after curing, it is preferable to use 30 mol% or more of the compound of formula (2), more preferably 50 mol% or more, and most preferably 70 mol% or more.
[0038] Preferred examples of such formula (2) include compounds represented by the following formulas (2-1) to (2-14).
[0039] TIFF0007651988000005.tif14498 TIFF0007651988000006.tif102119 TIFF0007651988000007.tif203130 TIFF0007651988000008.tif103151
[0040] In formulas (2-1) to (2-14), R 10 and R 11 Each of R independently represents hydrogen or alkyl having 1 to 6 carbon atoms. 10 and R 11 At least one of is hydrogen.
[0041] The polymer of the present invention may contain a known epoxy compound other than the compound represented by formula (1) as a part of its raw material. As such a known epoxy compound, it is preferable to select a bifunctional epoxy compound in order to keep the molecular weight of the polymer at a certain level or higher and maintain liquid crystallinity. As specific examples of such compounds, it is more preferable to use liquid crystal epoxy compounds represented by the following formulae (LC-1) to (LC-12) in order to maintain the liquid crystallinity of the polymer.
[0042] TIFF0007651988000009.tif201113 TIFF0007651988000010.tif74125
[0043] The polymer of the present invention may contain a known curing agent other than the compound represented by formula (2) as a part of its raw material. As such a known curing agent, in order to keep the molecular weight of the polymer within a suitable range, it is preferable to select a bifunctional phenolic compound, an aromatic monoamine, a diamine consisting of an amino substituted with an alkyl group, and a dicarboxylic acid. In addition, in order to prevent the polymer of the present invention from being deteriorated by heating or the like, it is preferable to select a diamine consisting of a phenolic compound, an aromatic monoamine, and an amino substituted with an alkyl group from the above curing agents. Furthermore, in order to maintain the liquid crystallinity of the polymer of the present invention, it is most preferable to select a phenolic compound.
[0044] Such a suitable phenol compound includes a compound represented by the following formula (q-1). TIFF0007651988000011.tif3293
[0045] In formula (q-1), R 12 independently represent hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, or fluorine; and n1 represents an integer of 0 to 4.
[0046] The polymer of the present invention can be synthesized by a known polymerization method. For example, the compound represented by formula (2) can be converted into a phenolate by the action of a base, and the phenolate can be reacted with an epoxy compound. Alternatively, the polymer can be obtained by heating an epoxy compound containing a compound represented by formula (1) and a curing agent containing a compound represented by formula (2) in the presence of a curing accelerator. In this case, the latter method is preferably used because it produces less waste products by the reaction.
[0047] Examples of the curing accelerator include imidazole-based curing accelerators such as imidazole, 2-ethyl-4-methyl-1H-imidazole, 2-phenyl-4-methyl-1H-imidazole, 1,2-dimethylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole, phosphorus-based curing accelerators such as triphenylphosphine, and amine-based curing accelerators such as 2,4,6-tris(dimethylaminomethyl)phenol, triethylenediamine, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, and 1,8-diazabicyclo[5.4.0]undec-7-ene. Of these curing accelerators, it is preferable to use an imidazole-based curing accelerator because it has a curing temperature of 200°C or less and has high curability.
[0048] The amount of the curing accelerator in the polymerization reaction is not particularly limited. However, the minimum amount that can complete the polymerization reaction is preferable. Specifically, the amount is preferably 0.1% by weight to 10% by weight, more preferably 0.5% by weight to 5% by weight, based on the total amount of the epoxy compound used.
[0049] The polymer of the present invention can be polymerized with or without a solvent. However, it is preferable to use a solvent because of the ease of handling during polymerization. Examples of such solvents include 1,4-dioxane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, dipropylene glycol methyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, ethylene glycol diethyl ether, di ... Propylene glycol dimethyl ether, N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, dimethylsulfoxide, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether propionate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl lactate, ethyl lactate, butyl lactate, 2-ethylhexanol, 1-propanol, isobutyl alcohol, n-butanol, 2-pentanone, methyl isobutyl ketone, diisobutyl ketone, cyclopentanone, cyclohexanone, diacetone alcohol, ethylene glycol, etc. can be preferably used. The above-mentioned solvents may also be used in combination.
[0050] The molecular weight of the polymer of the present invention is not particularly limited, but from the viewpoint of improving heat resistance, the weight average molecular weight (Mw) is preferably 1000 or more, more preferably 2000 or more. When the polymer of the present invention is made into a composition, in order to maintain compatibility with other components and solubility in a solvent, the molecular weight is preferably 1,000,000 or less, more preferably 500,000 or less.
[0051] It is also preferable that the composition containing the polymer of the present invention contains a polymerization initiator. As such a polymerization initiator, known thermal radical initiators, photoradical initiators, etc. can be preferably used. Examples of such initiators include azo-based, peroxide-based, sulfur-based, and organic metal salt radical initiators. Maleimide derivatives can also be preferably used for the same purpose. Among these radical polymerization initiators, azo-based and maleimide derivatives are particularly suitable for use because they have high storage stability and the product after reaction does not deteriorate the properties of the material of the present invention.
[0052] The composition containing the polymer of the present invention may contain known compounds, polymers, etc., to the extent that the effects of the present invention are not impaired. As such compounds, liquid crystalline epoxy compounds represented by the following formulas (LC-1) to (LC-12) can be preferably used.
[0053] TIFF0007651988000012.tif212119 TIFF0007651988000013.tif74125
[0054] As other compounds, non-liquid crystal epoxy compounds represented by the following formulae (o-1) to (o-15) are preferably used.
[0055] TIFF0007651988000014.tif170104
[0056] In formula (o-6), Z 10 is a single bond, -CH 2 -, -O-, -S-, -CH(CH 3 )-, -C(CH 3 ) 2 -, -SO 2 - or -C(CF 3 ) 2 -It is.
[0057] TIFF0007651988000015.tif203109
[0058] In formula (o-7) and formula (o-8), Z 11 is >CH- or >CCH 3 -It is.
[0059] TIFF0007651988000016.tif140105
[0060] As other polymers, resins made of compounds represented by the following formulas (o-20) to (o-24) are also preferably used.
[0061] TIFF0007651988000017.tif81170
[0062] In formula (o-20), Z 12 and Z 13 are independently a single bond, -CH 2 -, -O-, -S-, -CH(CH 3 )-, -C(CH 3 ) 2 -, -SO 2 - or -C(CF 3 ) 2 -, n21 represents an integer from 1 to 5000, In formula (o-21) and formula (o-22), n21 represents an integer of 1 to 5000, n22 and n23 represent 0 or 1, and when n21 is 2 or more, it may be different for each repetition, R 20 and R 21 each independently represents 1,4-phenylene, 4,4'-biphenylene, or cyclopentadienylene; In addition, hydrogen on the aromatic ring in these formulas (o-20) to (o-22) may be replaced by methyl.
[0063] TIFF0007651988000018.tif104109
[0064] In formula (o-23) and formula (o-24), Z 14 are independently a single bond, -CH(CH 3 )- or -C(CH 3 ) 2 -, and n21 represents an integer of 1 to 5000. In addition, hydrogen on the aromatic ring in formula (o-23) and formula (o-24) may be substituted with methyl.
[0065] In order to achieve high thermal conductivity, which is an effect of the present invention, it is preferable to select the compounds represented by formulae (LC-1) to (LC-8) from the above-mentioned epoxy compounds and polymers.
[0066] In order to improve the heat resistance of the material of the present invention, it is preferable to use a curing agent in combination with the epoxy compound. As such a curing agent, all known compounds such as phenols, cyanate esters, amines, carboxylic acids, carboxylic acid esters, acid anhydrides, or thiols can be used. In this case, in order to suppress the curing of the composition at room temperature (20°C) and improve storage stability, it is preferable to use a phenol, cyanate ester, or amine compound as a curing agent.
[0067] The phenol-based curing agent is preferably at least one compound represented by the following formulae (p-1) to (p-6), since it does not significantly impair the liquid crystallinity of the composition and is easily available.
[0068] TIFF0007651988000019.tif42115 TIFF0007651988000020.tif56148 TIFF0007651988000021.tif10297
[0069] In the above formula (p-1), Ring B is benzene, naphthalene, anthracene, fluorene, or 9,9-diphenylfluorene, and in these rings B, any hydrogen may be replaced by alkyl having 1 to 3 carbon atoms or alkoxy having 1 to 3 carbon atoms; n31 is an integer between 2 and 4 inclusive.
[0070] In the above formula (p-2), n32 and n33 are integers of 1 to 3; Z 30is a single bond, an alkylene having 1 to 10 carbon atoms, -CH(CH 3 )-, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, -O-, -S-, or -SO 2 - represents Any hydrogen on the benzene ring may be replaced by alkyl having 1 to 3 carbon atoms; In the above formula (p-3) and formula (p-4), n34 is an integer of 1 or more and 5000 or less, n35 and n36 are independently 0 or 1, and when n34 is 2 or more, it may be different for each repetition. In formula (p-4), R 10 and R 11 each independently represents 1,4-phenylene, 4,4'-biphenylene, or cyclopentadienylene; In formula (p-5), n34 is an integer between 1 and 5000, In formula (p-6), n34 is an integer between 1 and 5000, Z 31 are independently a single bond, -CH(CH 3 )- or -C(CH 3 ) 2 -, and n34 is an integer from 1 to 5000. In addition, hydrogen on the aromatic ring in these formulas (p-3) to (p-6) may be replaced by methyl.
[0071] The amine-based curing agent is preferably at least one compound represented by the following formula (a-1) or (a-2), since it does not significantly impair the liquid crystallinity of the composition and is easily available. EZ 20 -(LZ)nLE (a-1) L 1 -Z 20 -LE (a-2) In the formulas (a-1) and (a-2), Each E is independently amino, an alkylamino group having 1 to 10 carbon atoms, a hydroxyl group, or a carboxy group, and at least one E is amino or an alkylamino group having 1 to 10 carbon atoms. Z 20 are independently a single bond, -O-, -NH-, -S-, or -SO 2 -, -CO 2 -, or alkylene having 1 to 12 carbon atoms. L is independently a single bond, cyclohexylene, phenylene, or naphthalene, and at least one hydrogen atom in these rings may be replaced by alkyl having 1 to 10 carbon atoms. Z is independently a single bond, -O-, -NH-, -S-, or -SO 2 - or -CO 2 -It is. L 1 is hydrogen, cyclohexyl, phenyl, or naphthyl, and at least one hydrogen in these rings may be replaced by an alkyl group having 1 to 10 carbon atoms. n is an integer from 0 to 7.
[0072] Examples of the compound represented by formula (a-1) include aliphatic polyamines having 2 to 12 carbon atoms, such as ethylenediamine, trimethylenediamine, tetramethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, p-xylenediamine, and m-xylenediamine; p-phenylenediamine, N-methyl-p-phenylenediamine, N-ethyl-p-phenylenediamine, N-propyl-p-phenylenediamine, N-butyl-p-phenylenediamine, 2,5-diaminotoluene, m-phenylenediamine, N-methyl-m-phenylenediamine, N-ethyl-m-phenylenediamine, N-propyl-m-phenylenediamine, and N-butyl-m-phenylenediamine. aromatic polyvalent amines such as diaminodiamine, 2,4-diaminotoluene, 2,6-diaminotoluene, o-phenylenediamine, 1,5-diaminonaphthalene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylether, 1,1-bis(4-aminophenyl)cyclohexane, 4,4'-diaminodiphenylsulfone, bis(4-aminophenyl)phenylmethane, m-tolidine, and o-tolidine; and alicyclic polyvalent amines such as 1,4-cyclohexyldiamine, 1,3-cyclohexyldiamine, 1,2-cyclohexyldiamine, and 1,3-bis(aminomethyl)cyclohexane.
[0073] Among these, p-phenylenediamine, N-methyl-p-phenylenediamine, N-ethyl-p-phenylenediamine, N-propyl-p-phenylenediamine, N-butyl-p-phenylenediamine, 2,5-diaminotoluene, m-phenylenediamine, N-methyl-m-phenylenediamine, N-ethyl-m-phenylenediamine, N-propyl-m-phenylenediamine, N-butyl-m-phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, and 4,4'-diaminodiphenyl sulfone are particularly preferred because they have good compatibility when made into a composition and excellent storage stability.
[0074] Examples of the compound represented by formula (a-2) include aliphatic amines having 2 to 12 carbon atoms, such as n-propylamine, n-butylamine, n-pentylamine, n-hexylamine, n-octylamine, and n-dodecylamine; aromatic amines, such as aniline, o-toluidine, m-toluidine, p-toluidine, 2,3-dimethylaniline, 2,4-dimethylaniline, 2,6-dimethylaniline, 2,4,6-trimethylaniline, 2-ethylaniline, 1-naphthylamine, and 1-amino-2-methylnaphthalene; and alicyclic amines, such as cyclohexylamine and 2-methylcyclohexylamine. Among these, aniline, o-toluidine, m-toluidine, p-toluidine, 2,3-dimethylaniline, 2,4-dimethylaniline, 2,6-dimethylaniline, 2,4,6-trimethylaniline, and 2-ethylaniline are particularly suitable because they have good compatibility when made into a composition and excellent storage stability.
[0075] Preferable carboxylic acid compound curing agents include phthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,2'-biphenyldicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and benzophenone-4,4'-dicarboxylic acid.
[0076] In the composition containing the polymer of the present invention, the ratio of the known epoxy compound and the curing agent is not particularly limited. In this case, in order to efficiently proceed with the reaction to improve heat resistance, the reactive groups of the epoxy compound and the curing agent are preferably in equimolar amounts. For example, in the case of epoxy:phenol, it is 1:1, and in the case of epoxy:amine, it is 2:1.
[0077] When the composition of the present invention contains the above-mentioned epoxy compound and curing agent, it is preferable that the composition further contains the above-mentioned curing accelerator in order to improve heat resistance.
[0078] The concentration of the curing accelerator in the composition of the present invention is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, based on the weight of the polymerizable compound of the present invention, in order to efficiently proceed with the reaction to improve heat resistance, and is preferably 5% by weight or less, more preferably 3% by weight or less, based on the weight of the polymerizable compound of the present invention, in order to avoid deterioration of reliability due to sublimation of the curing accelerator.
[0079] In the composition of the present invention, the content of other materials relative to the polymer of the present invention is not particularly limited, but is preferably 50% by weight or less, more preferably 30% by weight or less, and most preferably 20% by weight or less, relative to the weight of the polymer of the present invention, so as not to impair the effects of the present invention.
[0080] In order to exhibit the heat dissipation characteristics of the material for electronic devices of the present invention, the composition preferably exhibits liquid crystallinity in the range of 20° C. to 200° C. in a state in which the solvent has been removed, and more preferably exhibits liquid crystallinity in the range of 100° C. to 200° C.
[0081] [Inorganic filler] The composition of the present invention may contain an inorganic filler. Examples of the inorganic filler contained in the composition for electronic parts include nitrides such as aluminum nitride, boron nitride, and silicon nitride, which are high thermal conductive fillers. Diamond, graphite, silicon carbide, silicon, beryllia, magnesium oxide, aluminum oxide, zinc oxide, silicon oxide, copper oxide, titanium oxide, cerium oxide, yttrium oxide, tin oxide, holminium oxide, bismuth oxide, cobalt oxide, calcium oxide, aluminum nitride, boron nitride, silicon nitride, magnesium hydroxide, aluminum hydroxide, gold, silver, copper, platinum, iron, tin, lead, nickel, aluminum, magnesium, tungsten, molybdenum, and stainless steel may also be used as inorganic fillers or metal fillers. Preferred are boron nitride, aluminum nitride, and aluminum oxide. Boron nitride and aluminum nitride are preferred because they have a very high thermal conductivity in the planar direction, a low dielectric constant, and high insulation. Hexagonal boron nitride (h-BN) and aluminum nitride are particularly preferred.
[0082] The shape of the inorganic filler may be spherical, amorphous, fibrous, rod-like, cylindrical, plate-like, or tetrapod-like. The type, shape, size, and amount of the inorganic filler may be appropriately selected according to the purpose. For example, when the cured product (material for electronic components) formed from the composition for electronic components requires insulation, the inorganic filler may be conductive as long as it maintains the desired insulation.
[0083] The average particle size of the inorganic filler is preferably, for example, 0.1 to 200 μm. More preferably, it is 1 to 100 μm. If it is 0.1 μm or more, the thermal conductivity is good, and if it is 200 μm or less, the filling rate can be increased. In this specification, the average particle size is based on particle size distribution measurement by laser diffraction / scattering method. That is, using analysis based on the Fraunhofer diffraction theory and the Mie scattering theory, when a powder is divided into two at a certain particle size by a wet method, the diameter at which the larger side and the smaller side are equal in amount (volume basis) is defined as the median diameter.
[0084] The amount of inorganic filler added is preferably 20 to 95% by weight, for example, when used in a heat dissipation member. More preferably, it is 50 to 95% by weight. If it is 20% by weight or more, the thermal conductivity becomes high, which is preferable. If it is 95% by weight or less, the heat dissipation member does not become brittle, which is preferable.
[0085] The inorganic filler may be used as it is without modification. Alternatively, the inorganic filler may be used after its surface has been treated with a coupling agent. For example, boron nitride (h-BN) is treated with a silane coupling agent. In the case of boron nitride, since there is no reactive group on the plane of the particle, the silane coupling agent is bonded only to the periphery. Boron nitride treated with a coupling agent can form a bond with a polymerizable compound in the composition for electronic components, and this bond is thought to contribute to thermal conduction. Therefore, the coupling agent is preferably one that reacts with oxiranyl, oxetanyl, or a group possessed by a curing agent. For example, one having an amine, oxiranyl, or oxetanyl is preferable. Specifically, Sila Ace S310, S320, S330, S360, S510, and S530 manufactured by JNC Corporation are listed.
[0086] The inorganic filler may be treated with a coupling agent and then surface-modified with a compound having a polymerizable group such as epoxy (polymerizable compound). For example, boron nitride (h-BN) treated with a silane coupling agent is surface-modified with a polymerizable compound. If boron nitride surface-modified with a polymerizable compound can form a bond with the polymerizable compound or a curing agent in the composition for electronic components, this bond is thought to contribute to thermal conduction. For example, the polymerizable compound may be the polymerizable compound of the present invention represented by formula (1), or may be any other polymerizable compound.
[0087] The inorganic filler used in the composition of the present invention may be subjected to a coupling treatment. The method of the coupling treatment is described below. The coupling treatment can be performed by a known method.
[0088] An example is given below. First, inorganic filler particles and a coupling agent are added to a solvent. The mixture is stirred using a stirrer or similar device and then left to stand. After the solvent has dried, a heat treatment is performed under vacuum conditions using a vacuum dryer or similar device. Solvent is added to the inorganic filler particles, and the particles are pulverized by ultrasonic treatment. This solution is separated and purified using a centrifuge. After discarding the supernatant, solvent is added and the same operation is performed several times. The refined inorganic filler particles are dried in an oven to obtain a coupling-treated inorganic filler.
[0089] [Other components] Other components that may be contained in the composition of the present invention are not particularly limited, and examples thereof include a polymerizable compound having a polymerizable group other than epoxy, a non-polymerizable compound, a polymerization initiator, and a solvent.
[0090] The polymerizable compound having a polymerizable group other than epoxy is not particularly limited, and any known polymerizable compound can be used as long as it does not deteriorate the properties of the electronic material of the present invention. Among them, compounds that undergo radical polymerization, such as acrylic compounds and styrene-based compounds, can be preferably used, and these compounds that exhibit liquid crystallinity can be more preferably used.
[0091] When the composition of the present invention contains a compound that undergoes radical polymerization, such as an acrylic compound or a styrene-based compound, a radical polymerization initiator may be used. Examples of such radical polymerization initiators include the above-mentioned thermal radical initiators and photoradical initiators. Examples of the types of such initiators include azo-based, peroxide-based, sulfur-based, and organometallic salt radical initiators. Maleimide derivatives can also be preferably used for the same purpose. Among these radical polymerization initiators, azo-based and maleimide derivatives are particularly suitable for use because they have high storage stability and the product produced after reaction does not deteriorate the properties of the material of the present invention.
[0092] The composition of the present invention may contain a solvent.Preferred solvents include, for example, 1,4-dioxane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, dipropylene glycol methyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol diethyl ether, dipropylene glycol dimethyl ether, Examples of the solvent include N-methyl-2-pyrrolidone, dimethylformamide (DMF), dimethylacetamide, dimethylsulfoxide (DMSO), methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether propionate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl lactate, ethyl lactate, butyl lactate, 2-ethylhexanol, 1-propanol, isobutyl alcohol, n-butanol, 2-pentanone, methyl isobutyl ketone, diisobutyl ketone, cyclopentanone, cyclohexanone, diacetone alcohol, ethylene glycol, toluene, xylene, mesitylene, heptane, and tetrahydrofuran (THF). The solvent may be used alone or in combination of two or more.
[0093] Since the composition of the present invention has high polymerizability, a stabilizer may be added to facilitate handling. As such a stabilizer, any known stabilizer can be used without limitation. For example, hydroquinone, 4-ethoxyphenol, and 3,5-di-t-butyl-4-hydroxytoluene (BHT) can be used.
[0094] Furthermore, additives (oxides, etc.) may be added to adjust the viscosity or color of the composition for electronic parts. Examples include titanium oxide to make it white, carbon black to make it black, and silica fine powder to adjust the viscosity. In addition, to further increase the mechanical strength, inorganic fibers such as glass and carbon fiber, or their cloths, or synthetic fibers such as polyvinyl formal, polyvinyl butyral, polyester, polyamide, and polyimide, or supramolecules may be added.
[0095] [Semi-hardened sheet] The semi-cured sheet of the present invention can be obtained by applying a composition containing the polymer of the present invention to a substrate, etc., and then removing the solvent. The method for applying the composition of the present invention is not particularly limited, and examples thereof include spin coating, roll coating, caten coating, flow coating, printing, microgravure coating, gravure coating, wire bar coating, dip coating, spray coating, meniscus coating, offset printing, and inkjet printing.
[0096] The temperature at which the solvent is removed when preparing the semi-cured sheet is preferably lower than the temperature at which such a reaction occurs in order to suppress the reaction of the crosslinking group. For example, in the structure represented by formula (3), R 2 When a crosslinking group in which all of are hydrogen is selected, the temperature is preferably 170° C. or less, more preferably 160° C. or less. When the reaction of the crosslinking group is carried out using a radical initiator, the temperature at which the solvent is removed is preferably equal to or lower than the temperature at which the radical initiator acts.
[0097] In order to improve the heat dissipation properties of the material of the present invention, it is more preferable that the molecules constituting the semi-cured sheet are arranged in a highly ordered manner. Therefore, it is more preferable that the temperature at which the solvent is removed when preparing the semi-cured sheet is within a temperature range at which the composition containing the polymer of the present invention exhibits a liquid crystal phase.
[0098] In order to improve the heat dissipation properties of the material of the present invention, it is also preferable to compress the semi-cured sheet of the present invention. The pressure during compression molding is 50 to 500 kgf / cm. 2 is preferable, and more preferably 70 to 250 kgf / cm 2 In principle, the higher the pressure during curing, the better. However, it is preferable to select an appropriate pressure depending on the purpose, such as the fluidity of the composition and the anisotropic control of the thermal conductivity of the material.
[0099] In order to improve the heat dissipation property of the material, it is preferable to heat the material during compression molding. More preferably, the heating temperature is within a temperature range in which the composition containing the polymer of the present invention exhibits a liquid crystal phase.
[0100] The semi-cured sheet can be cut into a desired shape and placed between suitable components to be bonded together. The semi-cured sheet bonded in this manner can be further cured by heating or the like to obtain a heat dissipation component.
[0101] [Heat dissipation materials] The heat dissipation member of the present invention can be obtained by curing the semi-cured sheet of the present invention. The heat dissipation member of the present invention can also be obtained by directly heating and curing the composition containing the polymer and / or inorganic filler of the present invention. Curing proceeds by three-dimensional crosslinking of the polymer of the present invention. In the case of a composition containing a low molecular weight component other than the polymer, curing also proceeds by polymerization of the low molecular weight at the same time as three-dimensional crosslinking.
[0102] In order to improve the heat dissipation properties of the heat dissipation member of the present invention, the curing temperature is preferably within a temperature range in which the composition and semi-cured sheet of the present invention exhibit a liquid crystal phase. In addition, the composition and semi-cured sheet of the present invention may have a liquid crystal temperature range that increases as the curing proceeds to a certain extent. In such a case, the composition and semi-cured sheet may be cured in the increased liquid crystal temperature range. The curing temperature may be constant or may be increased or decreased stepwise.
[0103] The heat curing temperature is in the range of 20°C to 350°C, preferably 50°C to 250°C, and more preferably 100°C to 200°C. The curing time is in the range of 5 seconds to 10 hours, preferably 1 minute to 8 hours, and more preferably 5 minutes to 5 hours. After polymerization, slow cooling is preferable to suppress stress distortion, etc. Also, a reheating treatment may be performed to relieve distortion, etc.
[0104] A crosslinking agent may be added to further crosslink the polymer. This makes it possible to obtain a polymer (cured product) that is extremely excellent in chemical resistance and heat resistance. As such a crosslinking agent, any known agent may be used without limitation, and an example of such an agent is trimethylolpropane tris(3-mercaptopropionate).
[0105] The heat dissipation member of the present invention can be used in the form of a sheet, film, thin film, fiber, molded product, etc. Preferred forms are a film and a thin film. A film and a thin film can be obtained by polymerizing the composition of the present invention in a state where the composition is applied to a substrate or sandwiched between substrates. A film can also be obtained by press molding the semi-cured sheet of the present invention. In this specification, the thickness of the sheet is 1 mm or more, the thickness of the film is 5 μm or more, preferably 10 to 900 μm, and more preferably 20 to 800 μm, and the thickness of the thin film is less than 5 μm. The thickness may be appropriately changed depending on the application.
[0106] The heat dissipating member of the present invention has excellent properties such as high thermal conductivity, chemical stability, heat resistance, hardness, mechanical strength, etc. Therefore, it is useful for heat dissipating plates, heat dissipating sheets, heat dissipating films, heat dissipating coatings, heat dissipating adhesives, heat dissipating molded products, etc.
[0107] The material of the present invention has been described as being used as a heat dissipation member, but the use of the material of the present invention is not limited to heat dissipation members. For example, the material may be used as a sealing material or an adhesive material.
[0108] [Electronic components] When the heat dissipation member of the present invention is used as a material for electronic components, the heat dissipation member is placed on the electronic device so as to contact the heat generating portion. The shape of the heat dissipation member may be any of a heat dissipation plate, a heat dissipation sheet, a heat dissipation film, a heat dissipation adhesive, a heat dissipation molded product, etc. In this way, the heat generated in the electronic device is dissipated by the heat dissipation member, and failure due to heat is avoided, thereby extending the life of the electronic device equipped with the electronic device.
[0109] Examples of electronic devices include semiconductor elements. The heat dissipation material has high thermal conductivity, high heat resistance, and high insulation. Therefore, it is particularly effective for insulated gate bipolar transistors (IGBTs), which require a more efficient heat dissipation mechanism due to their high power consumption. IGBTs are a type of semiconductor element, a bipolar transistor with a MOSFET built into the gate, and are used for power control. Examples of electronic devices equipped with IGBTs include the main conversion element of a high-power inverter, an uninterruptible power supply, a variable voltage variable frequency control device for an AC motor, a control device for a railway vehicle, electric transport equipment such as hybrid cars and electric cars, and an induction cooker.
[0110] [Method for synthesizing the compound represented by formula (2)] The compound represented by formula (2) can be synthesized by combining known methods in organic synthetic chemistry. Methods for introducing the desired polymerizable group and ring structure into the starting material are described in, for example, Houben-Weyl, Methods of Organic Chemistry, Georg Thieme Verlag, Stuttgart, Organic Syntheses, John Wiley & Sons, Inc., Organic Reactions, John Wiley & Sons, Inc., Comprehensive Organic Synthesis, Pergamon Press, and New Experimental Chemistry Course (Maruzen). Also, JP 2006-265527 A may be referenced. Some of the methods are also disclosed in the following examples. EXAMPLES
[0111] The present invention will be described in detail below using examples. However, the present invention is not limited to the contents described in the following examples. Unless otherwise stated, measurements were performed at 23°C.
[0112] [Melt point measurement of compounds] The measurement was performed using a polarizing microscope (Nikon) equipped with a hot stage (Mettler Toledo). The polarizing microscope measurement was performed under crossed Nicols. The temperature rise rate was 3°C / min. The melting point was determined as the temperature at which the crystals started to melt and at which they were completely melted.
[0113] [NMR measurement] NMR was measured using a VARIAN NMR SYSTEM manufactured by VARIAN. 1 The magnetic field strength for H NMR measurements was 500 MHz, and the sample was CDCl 3The compound was dissolved in a deuterated solvent such as tetramethylsilane, and the measurement was carried out at room temperature. The number of measurements was 8. The internal standard was tetramethylsilane. In the NMR symbols, s means singlet, d means doublet, t means triplet, m means multiplet, and br means broad.
[0114] [Confirmation of polymer liquid crystallinity] The polymer solution was dropped onto a glass plate, and the glass plate was placed on a hot stage at 130°C and left for 30 minutes to evaporate the solvent. The obtained sample was observed under crossed Nicols using a polarizing microscope. The sample was heated from 20°C to 200°C at a heating rate of 5°C / min. The magnifications of the eyepiece and objective lens were 10x10. When light leakage due to scattering was visually observed in more than half of the observation area, it was determined that liquid crystallinity was present.
[0115] [Measurement of polymer weight average molecular weight] The measurement was carried out by GPC analysis. The measurement was carried out using a liquid chromatograph (LC10A) manufactured by Shimadzu Corporation under the following conditions. The molecular weight was calibrated using GPC STANDARD P-82 (Showa Denko K.K.) as the standard solution. Measurement conditions: detector; RI, column; GPC KD-803 (Showa Denko K.K.), mobile phase; DMSO, flow rate; 0.5 ml / min, column oven temperature; 40°C, sample injection volume; 20 μL.
[0116] [Confirming the solvent resistance of materials] The polymer was dissolved in DMF to obtain a solution of about 20% by weight. Three to four drops of this polymer solution were dropped onto a glass slide. The glass slide was heated on a hot plate at 130°C for five minutes to evaporate the solvent, and then heated at 200°C for 40 minutes. After cooling to room temperature, the obtained film was placed in DMF (30 ml) and left to stand for 30 minutes. After removing from the DMF, the film was washed with about 20 ml of ethanol and vacuum dried in an oven at 100°C for three hours. The remaining film rate was calculated from the weight of the film before immersion in DMF and the weight of the film after immersion in DMF and drying. Residual membrane rate (%) = 100 × membrane weight after DMF treatment / membrane weight before DMF treatment
[0117] [Measurement of thermal conductivity] A sample consisting of resin only: NETZSCH LFA467 HyperFlash was used to measure the thermal diffusivity (α, m 2 The thermal diffusivity was measured in the thickness direction and in the in-plane direction of the sample. The specific heat (c, J / (Kg)) and density (ρ, g / m 3 ) and the thermal conductivity (W / m K) was calculated according to the following formula: κ = α × c × ρ At this time, the specific heat was measured using a DSC type high sensitivity differential scanning calorimeter Thermo Plus EVO2 DSC-8231 manufactured by Rigaku Corp. The specific gravity was measured using a specific gravity scale type specific gravity meter DME-220 manufactured by Shinko Denshi Co., Ltd. Filler-containing sample: The thermal diffusivity in the thickness direction of the sample was measured using an ai-Phase Mobile 1u thermal diffusivity measuring device manufactured by ai-Phase Co., Ltd. The specific heat and density of the sample were also measured in the same manner as above. From these values, the thermal conductivity was calculated in the same manner as above.
[0118] [Hardening agent and epoxy compound] As the curing agent represented by formula (2), compounds represented by the following formulas (2-1-1), (2-5-1), and (2-9-1) were used. These compounds were synthesized as described below. In addition, 4,4'-dihydroxybiphenyl (DHB) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. was used. Furthermore, TP was synthesized according to JP 2018-070553 A. As the compound represented by formula (1), Denacol EX-810 (manufactured by Nagase Chemtex Corporation) and the compound represented by formula (1-1) were used. The compound represented by formula (1-1) was synthesized according to Chemistry - A European Journal, vol. 14, p. 7988 (2008). The compounds represented by the following formulae (2-1-1), (2-5-1), and (2-9-1) can be crosslinked by their lateral vinyl groups, whereas DHB cannot be crosslinked because it does not have a lateral crosslinkable group. TIFF0007651988000022.tif2198 TIFF0007651988000023.tif20110 TIFF0007651988000024.tif20131 TIFF0007651988000025.tif1495 TIFF0007651988000026.tif22104 TIFF0007651988000027.tif1590 TIFF0007651988000028.tif1369
[0119] [Cure accelerator] Imidazole was manufactured by Tokyo Chemical Industry Co., Ltd. and was used as is without purification.
[0120] [Example 1] Synthesis of the compound represented by formula (2-5-1) TIFF0007651988000029.tif24169
[0121] In the above formula, THPO is tetrahydro-2H-pyran-2-yloxy, and PPTS represents pyridinium p-toluenesulfonate.
[0122] 1.00 g (3.81 mmol) of 2,5-dibromostyrene, 1.86 g (8.38 mmol) of 4-(Tetrahydro-2H-pyran-2-yloxy)phenylboronic Acid, 0.220 g (0.190 mmol) of tetrakistriphenylphosphine palladium(0), and Na 2 CO 3The mixture of 1.62 g (15.3 mmol) was refluxed in dimethoxyethane (20 ml) under a nitrogen stream for 3 hours. 2,5-Dibromostyrene was synthesized according to the Journal of American Chemical Society, vol. 134, p. 16131 (2012). After the reaction was completed, the reaction solution was cooled, and 60 ml each of pure water and toluene were added. The organic layer was separated, washed twice with the same amount of pure water, and then washed with anhydrous MgSO 4 After filtration and distillation of the solvent under reduced pressure, the resulting product was purified by column chromatography (silica gel, toluene / ethyl acetate=10 / 1) to obtain compound (2-5-1-a). Yield: 1.26 g (72%).
[0123] A mixture of 1.57 g (3.43 mmol) of compound (2-5-1-a) and 346 mg (1.38 mmol) of pyridinium p-toluenesulfonate was stirred in a tetrahydrofuran (THF) / methanol (10 ml / 10 ml) mixed solvent at room temperature for 2 days. Ethyl acetate (30 ml) and pure water (30 ml) were added and the layers were separated. The organic layer was washed with pure water (20 ml) and then diluted with anhydrous MgSO 4 After filtration and distillation of the solvent under reduced pressure, the resulting product was purified by recrystallization (ethanol / toluene) to obtain compound (2-5-1). Yield: 833 mg (84%).
[0124] Melting point(℃):191-194. 1 H-NMR (ppm, CDCl 3 );7.77(d,1H,J=2.50Hz),7.56-7.54(m,2H),7.49(dd,1H,J=8.00,2.50Hz),7.32(d,1H,J=8.00Hz),7.28-7.25(m,2H) ),6.95-6.88(m,4H),6.80-6.75(m,1H),5.76(dd,1H,J=17.50,1.50Hz),5.23(dd,1H,J=11.0,1.00Hz),4.82(brs,2H)
[0125] [Example 2] Synthesis of the compound represented by formula (2-9-1) TIFF0007651988000030.tif67168
[0126] In the above formula, Tf represents trifluoromethanesulfonyl, and THP and PPTS have the same meanings as above.
[0127] To a solution of 2.00g (9.34mmol) of 3-formyl-4,4'-dihydroxybiphenyl and 6.6ml of pyridine in methylene chloride (20ml), 3.4ml (20.7mmol) of anhydrous trifluoromethanesulfonic acid was added at room temperature or lower. After stirring overnight, the reaction solution was poured into pure water (50ml) and extracted with toluene (50ml). The organic layer was washed with dilute hydrochloric acid, pure water, and sodium bicarbonate water (50ml each), and then dried over anhydrous magnesium sulfate. The organic layer was filtered, the solvent was distilled off under reduced pressure, and the resulting product was purified by column chromatography (toluene) to obtain compound (2-9-1-a). Yield 3.66g (82%). In the above reaction, 3-formyl-4,4'-dihydroxybiphenyl was synthesized according to Journal of Medicinal Chemistry, vol.52, p.858(2009).
[0128] Compound (2-9-1-a) (2.00 g, 4.18 mmol) was reacted with 4-(Tetrahydro-2H-pyran-2-yloxy)phenylboronic Acid in the same manner as in Example 1. The resulting product was purified by column chromatography (silica gel, toluene) to obtain compound (2-9-1-b). Yield: 1.45 g (65%).
[0129] A solution of 294 mg (2.62 mmol) of t-BuOK in THF (10 ml) was added to a solution of 868 mg (2.43 mmol) of methyltriphenylphosphonium bromide in THF (10 ml) at 0°C or lower. After stirring at 0°C for 30 minutes, the mixture was cooled to -20°C, and 1.00 g (1.87 mmol) of compound (2-9-1-b) was added. After stirring at room temperature for 2 hours, the mixture was poured into pure water (50 ml) and extracted with toluene (50 ml). The organic layer was washed with pure water (50 ml) and then dried over anhydrous magnesium sulfate. The organic layer was filtered, the solvent was distilled off under reduced pressure, and the resulting product was purified by column chromatography (toluene) to obtain compound (2-9-1-c). Yield 857 mg (yield 86%).
[0130] Compound (2-9-1) was synthesized using 850 mg (1.60 mmol) of compound (2-9-1-c) in the same manner as in Example 1. The product was purified by recrystallization (ethanol / toluene) to obtain compound (2-9-1). Yield: 512 mg (88%).
[0131] Melting point (℃): 250℃ or higher 1 H-NMR (ppm, CDCl 3 );7.87(d,1H,J=1.50Hz),7.73-7.70(m,2H),7.66-7.62(m,2H),7.58(dd,1H,J=7.50,2.00Hz),7.57-7.54(m,2H),7.37(d,1H,J=8.00H z),7.30-7.27(m,2H),6.95-6.89(m,4H),6.79(dd,1H,J=17.0,11.0Hz),5.79(d,1H,J=17.0Hz),5.26(d,1H,J=11.5Hz),4.80(brs,2H).
[0132] [Example 3] Synthesis of the compound represented by formula (2-1-1) A mixture of 2.00 g (9.34 mmol) of 3-formyl-4,4'-dihydroxybiphenyl, 4.7 g (56 mmol) of 3,4-dihydro-2H-pyran, and 0.47 g (1.9 mmol) of PPTS was dissolved in CH2 Cl 2 The mixture was stirred overnight at room temperature in 20 ml of water. 30 ml of saturated sodium bicarbonate water was added to the reaction solution, and the organic layer was separated. The organic layer was dried over anhydrous magnesium sulfate and then filtered. The solvent was removed under reduced pressure, and the resulting product was purified by column chromatography (toluene:ethyl acetate=10:1) to obtain compound (2-1-1-a). Yield: 244 mg (yield 7.9%).
[0133] Compound (2-1-1-a) was converted to compound (2-1-1-b) in the same manner as in Example 2. The crude product was purified by column chromatography (heptane:toluene=1:1→toluene). Yield: 86%.
[0134] Compound (2-1-1-b) was converted to compound (2-1-1) in the same manner as in Example 2. The crude product was purified by column chromatography (toluene:ethyl acetate=2:1). Yield: 100%.
[0135] Melting point(℃):138.0-145.7. 1 H-NMR (ppm, CDCl 3 );7.54(d,1H,J=2.50Hz),7.44-7.41(AA'BB',2H),7.31(dd,1H,J=8.00,2.50Hz),6.97(dd,1H,J=17.50,10.50Hz),6.91 -6.87(AA'BB',2H),6.85(d,1H,J=8.50Hz),5.80(d,1H,J=18.00Hz),5.41(d,1H,J=11.00Hz),4.99(s,1H),4.76(s,1H).
[0136] [Example 4] Synthesis of liquid crystalline polymers A mixture of 1.4428g (3.959mmol) of the compound represented by formula (2-9-1) synthesized in Example 2, 0.6860g (3.938mmol) of EX-810, and 0.0510g of imidazole was reacted in methoxyethanol (2.1g) at 120°C for 1 hour. After cooling, ethanol (10ml) was added to the reaction solution and filtered. The obtained polymer (polymer 3) was dried under reduced pressure and dissolved in DMF (4.2g). The liquid crystallinity was confirmed using this polymer solution, and the polymer 3 was a liquid crystal polymer and maintained a liquid crystal state from 100°C to 200°C or higher. The weight average molecular weight of this polymer was 4500.
[0137] [Example 5] to [Example 8] In the same manner as in Example 4, polymers exhibiting liquid crystallinity in the following Examples 5 to 8 were synthesized. The results are shown in Table 1. At this time, the molar ratio of the curing agent to the epoxy compound was 1:1. The values in parentheses for the curing agent in Table 1 are the molar ratios of each curing agent in the total curing agent. Example 4 is also shown again.
[0138] Table 1. Liquid crystallinity loss temperature and weight average molecular weight of each polymer TIFF0007651988000032.tif73148
[0139] [Comparative Example 1] A polymer was synthesized from an equimolar mixture of DHB and EX-810 in the same manner as in Example 4. The weight average molecular weight of this polymer was 5200. This polymer ref1 was a liquid crystalline polymer, but when heated to 145°C, it lost its liquid crystallinity.
[0140] Comparison of Examples 4 to 8 with Comparative Example 1 shows that the polymer of the present invention has a high liquid crystal loss temperature and good heat resistance.
[0141] [Example 9] to [Example 12] and [Comparative Example 2] The solvent resistance of the polymers used as heat dissipation members was examined using the above polymers 5 to 8 and polymer ref 1. The results are shown in Table 2.
[0142] Table 2. Solvent resistance of each polymer TIFF0007651988000033.tif41143
[0143] It is found that the membrane using the polymer of the present invention has high solvent resistance, as compared with Examples 9 to 12 and Comparative Example 2. This is believed to be because, when the polymer of the present invention is formed into a membrane, double bonds in the styrene skeleton are polymerized with each other, and crosslinking occurs between the polymers.
[0144] [Example 13] Measurement of thermal conductivity of sheets prepared from polymers A 20 wt% DMF solution of polymer 5 was applied to an aluminum substrate with a thickness of 1 mm that had been treated with a release spray. The substrate was then left at 130°C for 30 minutes to remove the solvent. The formed film was then peeled off from the aluminum substrate. Three of these films were then stacked and held for 1 hour at a pressure of 5 MPa in a compression molding machine (IMC-19EC, manufactured by Imoto Machinery Co., Ltd.) heated to 150°C, and a square piece with a thickness of approximately 900 μm was taken out as a heat dissipation member. The thermal conductivity of this heat dissipation member 5 was 0.81 W / m·K and 0.42 W / m·K in the in-plane direction and thickness direction of the sample, respectively.
[0145] [Example 14] to [Example 16] The thermal conductivity of the heat dissipation members was measured using polymers 6 to 8 in the same manner as in Example 13. Example 13 is shown again in the table.
[0146] Table 3. Thermal conductivity of the heat dissipation member of the present invention TIFF0007651988000034.tif36140
[0147] [Example 17] Preparation of filler-containing samples 20 ml of a 20 wt % DMF solution of polymer 5 was measured out, and 6.0 g of boron nitride particles (PolarTherm PTX-25, manufactured by Momentive Performance Materials Japan, Ltd.) was added and mixed well. This sample was formed into a film in the same manner as in Example 13. The thickness of this heat dissipation member (filler-containing heat dissipation member 5) was 820 μm, and the thermal conductivity was 6.7 W / m K.
[0148] [Example 18] to [Example 19] Filler-containing heat dissipation members 6 and 7 were prepared and their thermal conductivity was measured in the same manner as in Example 17, except that polymers 6 and 7 were used instead of polymer 5. The results are shown in Table 4, which lists Example 17 again.
[0149] Table 4. Thermal conductivity of heat dissipation materials containing fillers TIFF0007651988000035.tif31141
[0150] As described above, it is understood that the technology disclosed in the present invention provides high thermal conductivity. [Industrial Applicability]
[0151] The technology of the present invention can be suitably used for packaging materials for semiconductor devices, and can also be used as an alternative to other epoxy resins, such as adhesives.
Claims
1. A linear polymer obtained from an epoxy compound and a curing agent, which has a temperature range in which it exhibits liquid crystallinity between 100°C and 200°C, and which also has a vinyl, acrylic, ethynyl, allyl, or vinyloxy functional group as a crosslinkable functional group.
2. The polymer of claim 1 , wherein the epoxy compound comprises a compound represented by formula (1) and the curing agent comprises a compound represented by formula (2). In formula (1), R 1 is an alkylene having 2 to 12 carbon atoms, At this time, R 1 Not adjacent to -CH 2 - may be replaced by -O-, -CH 2 -CF 2 May be replaced with -. In formula (2), R 2 are independently hydrogen, alkyl having 1 to 5 carbon atoms, alkoxy having 1 to 5 carbon atoms, or a group represented by formula (3), At this time, R 2 At least one of the above is a group represented by formula (3), and n is an integer of 0 to 3. In formula (3), R 3 are independently hydrogen or alkyl having 1 to 12 carbon atoms, and * represents the bonding position to the aromatic ring.
3. In the compound represented by formula (1), R 1 The polymer according to claim 2 , wherein: is an alkylene having 4 to 12 carbon atoms; and in the compound represented by formula (2), n is 2 or 3.
4. A composition comprising the polymer of any one of claims 1 to 3.
5. The composition of claim 4 further comprising an inorganic filler.
6. The composition of claim 5, wherein the inorganic filler is aluminum oxide or boron nitride.
7. A semi-cured sheet using the composition according to any one of claims 4 to 6.
8. A heat dissipation component obtained by curing the composition according to any one of claims 4 to 6.
9. A monomer composition of an epoxy compound and a hardener that provides a polymer according to any one of claims 1 to 3.
Citation Information
Patent Citations
Production of cured heat-resistant resin
JP1995268068A
Thermosetting epoxy resin composition, its use, and its curative
JP1997302070A
Insulating composition and insulating sheet containing the same
JP2010018679A
Epoxy prepolymer, and epoxy resin composition, cured material, semi-cured material, prepreg and composite substrate using the epoxy prepolymer
JP2010084042A
Resin composition, resin sheet, resin cured product and resin substrate
JP2019123834A